Human Resource Planning in Education (Journal of Organizational Psychology, 2021)
Human resource management is about people and organizations, where the significance of group coordination and effective planning strategies work together for achieving success in meeting goals. In the field of higher education, universities and colleges have a crucial role in improving society overall, which is an understanding of moving forward positively through academic achievement and knowledge. By bringing innovative ideas to the forefront of educational attainment, there will be many other opportunities addressed within the framework of HR planning in education. It is a strategic process in many ways, with one of the main issues being an organizational concern. The goals and objectives of schools will need to align effectively with the approaches that HR planning carries out in practice. This essay focuses on the discussion through a unique lens of analysis, including how mission statements and HRM strategies cooperate to improve student performance outcomes.
Keywords: organizational psychology; human resources, strategy, education, management, planning